Non-equilibrium thermodynamics and statistical mechanics - Attard, Phil (Oxford University Press, 2012)
This title builds from basic principles to advanced techniques, and covers the major phenomena, methods, and results of time-dependent systems. It is a pedagogic introduction, a comprehensive reference manual, and an original research monograph--